Speed of processing training to improve cognition in moderate to severe TBI: a randomized clinical trial - Chiaravalloti, Nancy D.; Costa, Silvana L; Armknecht, Caroline; Costanza, Kristin; Wallace, Sean; Moore, Nancy B.; DeLuca, John (Frontiers in Neurology, 2024)
Background Moderate to severe traumatic brain injury (TBI) often results in cognitive deficits. Processing speed (PS) deficits are common, exerting a significant impact on daily life. Few studies have examined the efficacy of cognitive rehabilitation specifically for PS deficits in moderate to severe TBI. Objective Examine the efficacy of Speed of Processing Training (SOPT) in moderate to severe TBI. This protocol is a 10-session behavioral intervention for PS deficits that has been successfully used with other cognitively impaired populations. Methods This double-blind, placebo-controlled, randomized clinical trial included 46 participants with moderate to severe TBI, 22 randomly assigned to the treatment group and 24 to the placebo-control group. Baseline and follow-up measures included a task similar to the training task (UFOV), measures of near transfer (neuropsychological measures of processing speed: Symbol Digit Modalities Test (SDMT), Wechsler Adult Intelligence Scale-IV (WAIS-IV) Symbol Search, WAIS-IV Coding) and measures of far transfer [neuropsychological measures of learning and memory: the California Verbal Learning Test-II (CVLT-II), Memory Assessment Scales - Prose Memory (MAS-PM)]. Results Significant improvement from pre-to post-SOPT was observed on all subtests of the UFOV, which is similar to the training task. There was no significant difference on neuropsychological measures of PS or new learning and memory post-treatment. Neuropsychological assessment 6-months post-treatment showed no significant change in PS ability over time. Monthly booster sessions did not impact performance at the 6-month follow-up. Conclusion Consistent with the SOPT literature, SOPT improves PS ability as measured by the UFOV, a task similar to the training task, in moderate to severe TBI. However, neither near nor far transfer was noted. That is, no improvement was noted on neuropsychological measures of PS.